Model Pembelajaran Think Pair Share dalam Meningkatkan Kualitas Pembelajaran Pendidikan Agama Islam di SMK Plus - Faiqoh Faiqoh (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2021)
The kind of research is used qualitative research. This research focuses on their analysis to make deductive and inductive conclusion, and then the analysis about inter-phenomena observed with using logical. Based on the result of research: The implementation of think pair share model on students of SMK Plus Matholiul Anwar had some troubles. But, after giving action by using guidance, so think pair share model ran well. The quality of Islamic education learning before using think pair share model was very bad. But, after teacher gave action, the result was very good. Gradually, the next session quality of Islamic education was good. Students and teacher had difficult to implement think pair share model because it was rarely used in teaching and learning. After reading reference book and gave comprehensive guidance, finally the following session of think pair share model could implement ran well and good. Based on the discussion, it can be found that the quality of Islamic education by using think pair share model significant increase.